A segurança do usuário no transoperatório de cirurgia eletiva - Oliveira, Viviane Sousa de (2015)
Many challenges are noticed in the current context of surgeries, such as how to incorporate actions of quality and safety based on the risk management and enhance the arrangement of the processes to improve the quality and safety to consolidate the implantation of the taken initiatives. Based on the assumption that a lot of health assistance connected to the surgical user safety is executed, without being registered in a medical form or following the safety protocol, the objective of the study was to analyze the registrations of procedures related to safety in medical records of patients submitted to elective surgeries. This is a quanti-qualitative study, conducted in three general hospitals of a municipal district of the northwest of Paraná. The sample comprised 653 medical records of patients submitted to elective surgeries in 2012, selected by proportional stratified sampling. Data was collected using an instrument. The guideline of this study was the Surgical Safety Checklist suggested by the World Health Organization and the Donabedian referential process, the quantitative analysis used the descriptive statistics using simple and proportional frequency and association tests, and the qualitative analysis was based on the documental one. Results showed that in none of the three hospitals the WHO Surgical Safety Checklist was being used as form of institutional registration, and divergences were noticed in the forms used concerning the organization of the information in the logic proposed by it, considering that there was no sequence for checking and way of filling out the relevant information for each one of the three critical moments of the surgical assistance. Regarding the profile, for the most part, the data highlighted: average 44.6±21.0 years of age; female; general surgery as main medical specialty; use of general anesthesia; low permanence in the post-anesthetic recovery room; time of surgery less than 1 hour; the use of operative room between 1 and 2 hours and the time of hospitalization between 1 and 2 days; in 70.4% of the cases, the time of preoperative hospitalization was less than 24 hours; one hospital used identification label; none accomplished demarcation of surgical site. With relationship to the registration of safety's variables, it stood out: regarding the evaluation of the physical status of the patients the evaluation of upper respiratory system with classification of Mallampati in 55.7%, being 11% suggestive of difficult intubation; 45.2% with ASA I classification; 69.7% of the anti-microbial prophylaxis accomplished at the moment of surgery and 3.2% one hour before the incision; 99% of antisepsis of the surgical site; information gaps regarding the tricotomy; 1.3% of problems with materials and equipment. It is concluded that the assistance in elective surgeries follows the tendencies in the field, but, nor all the technological and scientific resources such as the WHO Surgical Safety Checklist are being used sufficiently on behalf of a safe introperative period. And, that there is relationship between variables of safety and structural conditions and of work process developed at the hospitals, evidencing fragilities and gaps to the light of the current national and international guidelines of safety.